After the end: reproduction and subversion of gender stereotypes in post-apocalyptic narratives - Pekserbes, Fulya (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: Within thelasttwodecades,somepost-apocalypticnarrativeswithprogressivegender rhetoric and strong, rebellious heroines have been adapted to screen. These critically acclaimed feministpost-apocalypticnarrativesmanagedtoleadchangewithinagenre that are commonly acclaimed to be white, cisgender, male-dominated. Through their storylines that center around the struggle for social and environmental justice in the face of patriarchy, oppression, and capitalism; and their heroines who lead the fight with not only strength and determination but also with care and compassion, these narratives succeeded to challenge the status quo, binary oppositions and value hierarchies. While seeing these representations of independent, strong and compassionate women who rebel against the patriarchal order within a genre that is commonly acclaimed to be dominated by men is extremely empowering, these narratives reproduce some gender essentialist, reductionist views of radical and cultural feminism such as women being nicer, kinder and more moralthanmen.This research suggests that within these narratives, while some aspects of this patriarchal gender norms are reimagined and reconstructed, some other deeply-seated ones remain unchallenged and taken for granted. In order to analyze this argument, this research will look into the waysthatgenderessentialistdiscoursehavebleedintotwo of the critically acclaimed feminist narratives of the last decade; The Hunger Games and Mad Max: Fury Road and try to unravel hidden essentialism thatmaybelurking within empowerment.

ÖZET: Son yirmi yıllık zaman zarfında, ilerici cinsiyet söylemi ve güçlü, asi kadın kahramanları ile öne çıkan birkaç kıyamet sonrası anlatı beyaz perdeye uyarlandı. İzleyiciler ve eleştirmenlerce beğenilen ve feminist olarak betimlenen bu kıyamet sonrası anlatılar, genellikle beyaz, natrans, heteroseksüel erkek egemen olarak kabul edilenbirtüriçindedeğişimeöncülüketmeyibaşardılar.Patriarki,toplumsal&politik baskı ve kapitalizm karşısında sosyal ve çevresel adalet mücadelesini merkeze alan hikayeleriyle ve sadece güç ve baskı ile değil, aynı zamanda özen ve şefkatle mücadeleye öncülük eden kadın kahramanları ile bu anlatılar, statükoya, ikili karşıtlıklara ve değer hiyerarşilerine meydan okumayı başardılar. Patriarkal düzene isyan eden bu bağımsız, güçlü ve yardımsever kadınları, erkeklerin egemenliğinde olduğu yaygın olarak kabul edilen bir tür içinde önemli rollerde görmek son derece güçlendirici olsa da, bu anlatılar aynı zamanda kadınların erkeklerden daha iyi, daha kibar ve daha ahlaklı olduğu gibi toplumsal cinsiyete dair bazı özcü, indirgemeci, radikal feminist görüşleri yeniden üretiyorlar. Bu araştırma, bu anlatılar içinde bazı ataerkil toplumsal cinsiyet normlarının yıkılıp, yeniden tasavvur ve inşa edildiğini, fakat bazı derinlere yerleşmiş olanların sorgulanmadan kabul edilip perdeye taşındığını ileri sürmektedir. Bu argümanı analiz etmek için, toplumsal cinsiyet özcü söylemin, son onyılıneleştirmenlercebeğenilenkıyametsonrasıfeministanlatılardan ikisine ve bu anlatılarda mevcut güçlendirilme ve cinsiyet eşitliği söylemlerine nasıl sızdığı incelenecektir; Açlık Oyunları ve Mad Max: Fury Road.
Sondan sonra: kıyamet sonrası anlatılarda toplumsal cinsiyet rollerinin yeniden üretimi ve yıkımı
Keywords: Film Araştırmaları; Cinsiyet Özcülüğü; Annelik Özgeciliği; Feminist Anaerkillik; Özen Ahlakı; Film Studies; Gender Essentialism; Maternal Altruism; Feminist Matriarchy; Ethics of Care